Implementation Of Indonesian Realistic Mathematics Approach To Improve Students Mathematic Skills - Edi Suherman; Irvan Irvan; Zulfi Amri (Indonesian Journal of Education and Mathematical Science, 2021)
This research is a quantitative research that aims to apply the Indonesian Realistic Mathematics Education (PMRI) approach in learning mathematics as an effort to improve the mathematics ability of high school students. Low math skills directs researchers how to improve math skills through the application of the PMRI approach using everyday life problems in learning mathematics. Mathematical skills in question are students' abilities in mathematics proficiency tests through conceptual understanding, reasoning, and problem solving exercises. This study aims to improve junior high school students through the PMRI approach in the teaching and learning process supported by appropriate learning tools. To achieve this, the method used in this study is a quantitative method with an experimental design. Meanwhile, to measure student responses and activities, this study used a qualitative approach. Quantitative data were analysed using statistical analysis techniques, namely t-test, while qualitative data were analysed using descriptive analysis techniques. The specific objective to be achieved in this research is to provide adequate teaching materials using the PMRI approach which innovatively supports the improvement of the mathematics abilities of junior high school students. Based on data analysis and hypothesis testing, there is a significant increase in students' mathematical abilities when using the PMRI approach rather than using the conventional approach. Furthermore, student responses and activities during the learning process with the PMRI approach are included in the specified category